Innovative Approaches in Pedagogy for Higher Education Classrooms - Sengupta, Enakshi; Blessinger, Patrick (Innovations in higher education teaching and learning, 2022)
This book highlights case studies and innovative teaching methods used by academics across the globe. It talks about how teaching staff should stimulate students' active engagement in their own learning processes, and discusses the approach of implementing a project-based learning activity that integrates learning in an authentic manner.